(untitled) (Research, Society and Development, 2022)
Weaning is a critical time for the young pig. The nutrient requirements of nursery pigs are affected by many factors such as weaning age, antigen exposure, and sex of the pig. Also, since feed intake is influenced by the learning abilities of the animal, any negative post-ingestive experiences with digestion may be linked to the feed and decrease feed intake. The present study aimed to evaluate the impact of the supplementation of different feed flavours for piglets during nursery phase on their performance and analyze the correlation between nursery performance and grower/ finisher performance and carcass traits. The use of flavored feed in nursery pens had a positive effect on voluntary feed intake and consequently overall nursery phase performance, which also impacted positively on piglet growth rates. Our results also indicated that there is a direct impact of the nursery end BW and finisher performance traits. Pigs that ate more gained more weight and were heavier at the end of nursery, also grew faster and were heavier at slaughter than the control pigs. This higher BW at slaughter also reflected on improved carcass performance traits. We can conclude that the use of feed flavours is an important tool to reduce post-weaning stress and enhance piglet performance during nursery which impacts positively on finisher output performance and carcass traits.